Blurred digital mammography images: an analysis of technical recall and observer detection performance - Ma, Wang Kei (2017)
Objective - Blurred images in full-field digital mammography are a problem in the UK Breast Screening Programme. Technical recalls may be due to blurring not being seen on lower resolution monitors used for review. This study assesses the visual detection of blurring on a 2.3-MP monitor and a 5-MP report grade monitor and proposes an observer standard for the visual detection of blurring on a 5-MP reporting grade monitor. Methods - 28 observers assessed 120 images for blurring; 20 images had no blurring present, whereas 100 images had blurring imposed through mathematical simulation at 0.2, 0.4, 0.6, 0.8 and 1.0 mm levels of motion. Technical recall rate for both monitors and angular size at each level of motion were calculated. χ2 tests were used to test whether significant differences in blurring detection existed between 2.3- and 5-MP monitors. Results - The technical recall rate for 2.3- and 5-MP monitors are 20.3% and 9.1%, respectively. The angular size for 0.2- to 1-mm motion varied from 55 to 275 arc s. The minimum amount of motion for visual detection of blurring in this study is 0.4 mm. For 0.2-mm simulated motion, there was no significant difference [χ2 (1, N = 1095) = 1.61, p = 0.20] in blurring detection between the 2.3- and 5-MP monitors. Conclusion - According to this study, monitors ≤2.3 MP are not suitable for technical review of full-field digital mammography images for the detection of blur.